2001
DOI: 10.1037/h0095053
|View full text |Cite
|
Sign up to set email alerts
|

Reducing psychiatric hospital use of the rural poor through intensive transitional acute care.

Abstract: A controlled study of the impact of brief, transitional acute care in reducing psychiatric treatment costs for people in rural areas is presented. Treatment emphasized home-based counseling and support, 24-hour rapid response, rural outreach, and intensive support management. The objective was to avert hospitalizations when possible, expedite discharge, and reduce likelihood of readmission, while maintaining comparable or superior clinical outcome. One-hundred eighty-two participants were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Study findings showed that the 90 participants who were randomly assigned to the transitional team had fewer total days of hospitalization than the 92 participants assigned to usual care (transitional team, 7.57± 9.42 days; routine care, 10.39±10.44 days, F=5.33, df=3 and 178, p=.002). No significant differences were found in symptoms, level of functioning, or social support (31). These findings parallel those obtained by most assertive community treatment teams in urban areas-that is, reduced hospitalizations but no consistent effects on psychosocial outcomes (25,42).…”
Section: Randomized Trials Of Assertive Community Treatmentsupporting
confidence: 72%
See 3 more Smart Citations
“…Study findings showed that the 90 participants who were randomly assigned to the transitional team had fewer total days of hospitalization than the 92 participants assigned to usual care (transitional team, 7.57± 9.42 days; routine care, 10.39±10.44 days, F=5.33, df=3 and 178, p=.002). No significant differences were found in symptoms, level of functioning, or social support (31). These findings parallel those obtained by most assertive community treatment teams in urban areas-that is, reduced hospitalizations but no consistent effects on psychosocial outcomes (25,42).…”
Section: Randomized Trials Of Assertive Community Treatmentsupporting
confidence: 72%
“…Recognizing that the name "assertive community treatment" itself was not sufficient to identify all relevant published studies, we developed a search strategy to identify relevant studies that was based on three program model criteria derived from prior literature reviews and implementation studies conducted in the United States (10,17,(25)(26)(27): team members had shared caseloads, most services were delivered directly rather than brokered to other community resources, and a psychiatrist or nurses were regular members of the team. Using this strategy, we searched the PsycINFO and PubMed Central databases from 1973 to 2005 and located six studies that met the criteria (28)(29)(30)(31)(32)(33). Although these studies represented a wide variety of settings and implementation strategies for rural assertive community treatment, we sought to present the strongest evidence about program effectiveness, so we selected only the studies that used a true experimental design.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a wide literature on how ACT works in rural (Meyer and Morrissey 2007;McDonel et al 1997;Becker et al 1999;Chandler et al 1996;Drake et al 1993;Dush et al 2001;Kane and Blank 2004;Santos et al 1993;Gold et al 2006) and urban areas (Lehman et al 1997;Dixon et al 1993;Cuddeback et al 2008Cuddeback et al , 2006Essock et al 2006;Ceilley et al 2006), there has been little research to date comparing rural and urban ACT teams to determine how they vary within this context. One study compared urban and rural ACT case managers' attitudes about critical ingredients of ACT and did not find significant differences (McGrew et al 2003).…”
Section: Introductionmentioning
confidence: 96%